The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/access.2022.3190863
|View full text |Cite
|
Sign up to set email alerts
|

Soft Robotic Grippers for Crop Handling or Harvesting: A Review

Abstract: Nowadays, harvesting delicate and high-value fruits, vegetables and edible fungi requires a large input of manual human labor. The relatively low wages and many health problems the workforce faces make this profession increasingly unpopular. Meanwhile, robotic systems that selectively harvest crops are being developed. Whilst the moving platform, manipulator, and recognition systems of such robots are studied the past few decades, research on the gripping end of such robots is only recently growing. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 124 publications
0
27
0
Order By: Relevance
“…where tč,i i−1 and Rč,i i−1 describe the translation and rotation from the base of the segment to the camera frame according to the PCC kinematic model for an estimated configuration of the the segment qi . T č,i i−1 (q č,i ) and Rč,i i−1 (q č,i ) are based on (1) and a function of the adjusted configuration q č,i referenced in (2).…”
Section: B Projection Into Pcc-kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…where tč,i i−1 and Rč,i i−1 describe the translation and rotation from the base of the segment to the camera frame according to the PCC kinematic model for an estimated configuration of the the segment qi . T č,i i−1 (q č,i ) and Rč,i i−1 (q č,i ) are based on (1) and a function of the adjusted configuration q č,i referenced in (2).…”
Section: B Projection Into Pcc-kinematicsmentioning
confidence: 99%
“…With their bodies entirely made of soft deformable materials, continuum soft robots are especially suited for application domains involving safe and robust interaction with humans and environment, and ranging from inspection, to healthcare and agriculture [1], [2]. To achieve these goals, soft robots must first master the art of controlling and sensing their body shape in space [3].…”
Section: Introductionmentioning
confidence: 99%
“…Stateoftheart progress in research and future challenges is docu mented in a wide range of review papers and book chapters addressing agriculture in general [1], [3], [4], [5] and specific application domains, including phenotyping [6], [7], [8] ara ble farming [9], livestock farming [10], greenhouse horticulture [2], orchard management [11], forestry [12], and food processing [13]. Review papers also address specific technologies in the context of agricultural robotics, such as computer vision [14], [15], active perception [16], unmanned aer ial vehicle technologies [17], [18], cov erage path planning in arable farming [19], and grasping and soft grasping [20], [21]. Some illustrative examples of agrifood robotics are documented in Figure 2.…”
Section: Challengesmentioning
confidence: 99%
“…Whilst advanced machinery has enabled the harvesting of many crops from barley to beetroot, many crops have thus far escaped automation [3]. This includes those that are delicate, fragile or have highly complex surrounding environments such as berries, salad, or grapes [4], and also those which do not ripen homogeneously. Despite over 30 years of research, harvesting robots have shown limited performance improvement [5].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there have been notable examples of robotic harvesting technologies for crops including strawberries [14,15], sweet peppers [16] and apples [17], examples remain limited [18,19]. Within these, repeated periods of field trials for early stage evaluation or training are commonly reported.…”
Section: Introductionmentioning
confidence: 99%